ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN EMKM TERHADAP PENYUSUNAN LAPORAN KEUANGAN UMKM: (Studi Kasus Usaha Sate Maranggi RK) - Imas Masitoh; Neng Tika Septika (Universitas Prof.Hazairin,SH Bengkulu, 2025)
The Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM) are designed to assist Micro, Small, and Medium Enterprises (MSMEs) in preparing simpler financial reports but still in accordance with applicable accounting principles. This study aims to analyze the application of SAK EMKM in the preparation of financial reports for MSME Sate Maranggi RK and to identify the obstacles faced by these business actors in implementing this standard. The research method used is a qualitative approach with interview techniques and case studies on MSME Sate Maranggi RK. The results of the study indicate that these MSMEs still have difficulty in understanding and implementing SAK EMKM due to limited accounting knowledge and minimal socialization from related parties. The conclusion of this study emphasizes the importance of education and assistance for MSME actors in implementing SAK EMKM. With the implementation of better accounting standards, MSMEs can increase financial transparency, facilitate access to capital, and strengthen their business competitiveness in the market